The Influence of Work Environment and Work Facilities on Employee Job Satisfaction at the Regional Public Drinking Water Company Tirta Darma Ayu Indramayu Head Office - Hasanah, Nesa Fitriyani; Damayanti, Fitria; Sonjaya, Nana Supriatna (Universitas Wiralodra, 2025)
Employee job satisfaction in public water utilities significantly impacts service delivery quality and organizational performance, yet limited research examines the simultaneous influence of physical work conditions and facility adequacy on satisfaction levels within Indonesian regional water companies. Objective: This study investigates the individual and combined effects of work environment and work facilities on employee job satisfaction at PDAM Tirta Darma Ayu Indramayu Head Office. Methods: A quantitative descriptive-associative approach was employed using simple random sampling of 59 employees from a population of 146 staff members. Data were collected through validated questionnaires and analyzed using correlation analysis, coefficient of determination, and hypothesis testing via SPSS 26. Results: Work environment demonstrated a very strong positive correlation with job satisfaction (r = 0.837, t-count = 11.527 > t-table = 1.672, p < 0.05). Work facilities showed a strong positive correlation with job satisfaction (r = 0.705, t-count = 7.498 > t-table = 1.672, p < 0.05). The combined variables exhibited a very strong correlation (R = 0.840, F-count = 67.308 > F-table = 3.16, p < 0.05) with 70.6% variance explanation (R² = 0.706). Conclusions: Both work environment and work facilities individually and simultaneously exert significant positive influences on employee job satisfaction, providing empirical evidence for prioritizing workplace condition improvements in public utility management strategies.